An isolated cardiac metastasis from colorectal adenocarcinoma. (11th January 2011) - Patel, M; Neal, C P; Berry, D P; Garcea, G
Abstract : Epidemiological information relating to cardiac metastases is predominantly based on autopsy studies. The reported incidence ranges from 2.3–18.3%. It is usually found in the presence of widely disseminated disease. Here, a case of an isolated, asymptomatic cardiac metastasis from colonic adenocarcinoma is reported. The metastasis was detected later, following bowel resection and was not amenable to surgical resection. The patient is receiving ongoing care from the oncology team.